The Harvard Catalyst Common Reciprocal IRB Reliance Agreement: An Innovative Approach to Multisite IRB Review and Oversight. Issue 1 (8th September 2014) - Winkler, Sabune J.; Witte, Elizabeth; Bierer, Barbara E.; on behalf of the Harvard Catalyst Regulatory Foundations, Ethics and Law Program
Abstract Reduction of duplicative Institutional Review Board (IRB) review for multiinstitutional studies is a desirable goal to improve IRB efficiency while enhancing human subject protections. Here we describe the Harvard Catalyst Master Reciprocal Common IRB Reliance Agreement (MRA), a system that provides a legal framework for IRB reliance, with the potential to streamline IRB review processes and reduce administrative burden and barriers to collaborative, multiinstitutional research. The MRA respects the legal autonomy of the signatory institutions while offering a pathway to eliminate duplicative IRB review when appropriate. The Harvard Catalyst MRA provides a robust and flexible model for reciprocal reliance that is both adaptable and scalable.